A preliminary approach based on numerical simulations for the design of a PWV-Varying arterial simulator. (December 2021) - Fuiano, Fabio; Fiori, Giorgia; Scorza, Andrea; Schmid, Maurizio; Conforto, Silvia; Sciuto, Salvatore Andrea
Abstract: Nowadays, in both scientific and medical communities, Pulse Wave Velocity (PWV) is commonly considered as a predicting factor of cardiovascular diseases. Such issue leads to the necessity of accurate PWV measurements as PWV non-local assessment is currently affected by low accuracy distance measurements. Despite the great interest on such predictor, a reference standard for PWV assessment is still awaited. In sight of the development of a reference standard able to reproduce PWV variations, the necessity arises of a mathematical model involving the main physical quantities influencing PWV. Therefore, the present study aims at giving a contribution in the development of such model as well as in the implementation of numerical simulations for the design of a sensorized PWV-varying arterial simulator as regards its metrological and physical characteristics. Despite the promising results, further developments could include a greater system parametrization, a system miniaturization as well as the investigation of other metrological characteristics.